Academic identity and crossing boundaries: the role of the Programme Director in postgraduate taught programmes. Issue 7 (9th November 2020) - Aitken, Gillian; O'Carroll, Sinéad
ABSTRACT: Taught postgraduate programmes (PGT) exist in a competitive global market and those leading such programmes have to chart a way through complex and often conflicting demands. Twenty-two Programme Directors (PDs) from one research-intensive university in the UK were interviewed individually about their experiences of leading PGT programmes. Interview transcripts were thematically analysed using Braun and Clarke's method and we consider results in relation to circus acts, chosen to conceptualise the complexity and diversity of activities undertaken by the PDs, specifically: clairvoyant, conjurer, blind-folded tight-rope walker, trapeze-artist, contortionist and seasoned performer. PDs described the diversity of the role and high levels of autonomy needed to successfully perform it, but also perceived the role to be under-valued and not well understood or supported. Academic identity was considered to be fluid and permeable, largely related to PGT programmes often being situated on the boundary between academic and professional organisations, leading to many boundary-spanning behaviours. Teaching and student contact were the most rewarding aspect of the role, albeit with a strong sense that these senior teaching roles were less valued than research posts. In the absence of obvious support structures, a clear sense of trust and academic citizenship was reported in the provision of mutual support of others in the same position. There is a need to mobilise this nascent community to establish a strong coherent voice for this academic role to inform planning both for the support of postgraduate students and for those delivering the teaching.